Analysis of the Facebook Page of the Ghana Police Service - Effah, Jonathan Owusu (UniMAC-GIJ, 2021)
The emergence of internet and access to technological gadgets has become important part of daily activities of individuals. Most importantly social media use has transformed the way individuals communicate, sustain friendships, live and work. Social media has become the platform where organisations build and retain relationship with their publics. The increased use of social media by organisations all over the world has led researchers and practitioners to seek to understand how best to employ it into communication strategies for effective communication delivery. This study analysed how the Ghana Police Service utilized their facebook page in communicating with their publics. The study was underpinned by the dialogic public relations theory. The study used the mixed method approach and purposive sampling technique. The study employed cyber ethnography to obtain data from the facebook page of the Ghana Police Service from January to June, 2021. The study generally found that, although the Ghana Police Service actively engaged their publics on facebook, there were some discrepancies in their inability to reply all comments but focused on replying to only positive ones. The study identified that some of these engagements spans from alerting the public on scammers, fake facebook accounts and information about the Ghana Police Service. It was noted that there were posts made each day by the Ghana Police Service on the facebook page which showed a good indication that the Ghana Police Service posted frequently on their facebook page each day. It was also observed that page visitors took advantage of the openness of the police to bully them and used invectives words irrespective of the importance of the posts. The study concluded that, the facebook page strengthened the Ghana Police Service to constantly engage with its publics for effective policing. in Ghana. The study recommends that the Ghana Police Service and public relation practitioners should take advantage of the numerous opportunity social media specifically facebook presents.
Thesis
Keywords: Facebook, Ghana Police Service, Ghana